Increasing the accuracy of glioblastoma subtypes: Factoring in the tumor's cell of origin - Nelander, Sven (Mol Cell Oncol, 2018)
The transcriptional classification of glioblastoma has proven to be a complex issue. In the absence of strong correlations between underlying genomic lesions and transcriptional subtype, there is a need to systematically understand the origins of the glioblastoma subtypes. A recent integrated analysis of data from both mouse models and patient-derived cells supports that the glioblastoma's cell of origin is important in shaping transcriptional diversity and tumor cell malignancy.